Contribution from cross-country skiing, start time and shooting components to the overall and isolated biathlon pursuit race performance - Luchsinger, H.; Kocbach, J.; Ettema, G.; Sandbakk, Ø. (PLOS ONE, 2020)
Biathlon is an Olympic sport combining 3-5 laps of cross-country skiing with rifle shooting, alternating between the prone and standing shooting positions between laps. The individual distance and the sprint are extensively examined whereas the pursuit, with start times based on the sprint results, is unexplored. Therefore, the current study aimed to investigate the contribution from start time, cross-country skiing time, penalty time, shooting time and range time to the overall and isolated performance in biathlon World Cup pursuit races.